PENELITIAN DAN PENGEMBANGAN TEKNOLOGI PRODUKSI BENIH PADI HIBRIDA DENGAN TETUA BETINA JANTAN MANDUL DAN TETUA JANTAN RESTORER YANG POTENSIAL - Djoko Murdono; Sonny Heru Priyanto; Joko Prihantono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2010)
Based on the availability of hybrid rice seeds which are needed by farmers and expensive prices and the interest of farmers around Banyubiru, Ambarawa, therefore this research was conducted. This research used restorer which come from seven local lines and two lines of Cytoplasmic Male Sterile (CMS) from China which were adapted in research location. The expectation on this research in long time is to produce local hybrid rice seeds from hybridization of both excellent line from China and excellent local varieties. The aim of this research are (1) to produce both potential CMS’s and potential restorers, (2) to produce parent hybrid rice which could produce Indonesia new hybrid varieties in long time. This research was conducted in Kayuwangi village, Banyubiru sub district, Semarang regency, from May to September 2009. Methods of line description and hybridization, and parent selection technique were based on combining ability of hybridization which were conducted to get tested parents. All material in this research were observed and evaluated. From this research can be concluded that: (1) candidate of both restorer and CMS has been got their description, which were adapted to the condition of rice field in Banyubiru, Semarang regency, (2) hybridization result of restorers and CMS’s have shown their combining ability, (3) effort to get restorer of CMS lines were not success. Suggestion which made were (1) Saving of seeds from first hybridization yield will be planted continuously in attempting to produce description of new hybrid varieties, (2) Doing continual research on variability of plant phenotype (F2) which show character of local CMS, (3) Doing back cross to relevant parents in efforts to maintain determined character of plant phenotype, and (4) Doing research of variation plant phenotype occurred, which could give maintainer lines.